Follicular expression of follicle stimulating hormone receptor variants in the ewe - Sullivan, Rachael R.; Faris, Brian R.; Eborn, Douglas; Grieger, David M.; Cino-Ozuna, Ada G.; Rozell, Timothy G. (My University, 2014)
Background: Several alternatively-spliced mRNA transcripts of the follicle stimulating hormone receptor (FSHR) have been identified in sheep, including FSHR-1 (G protein-coupled form), FSHR-2 (dominant negative form), and FSHR-3 (growth factor type-1 form). Our objective was to determine which of these variants is predominantly expressed in follicles collected from ewes at various times after estrus. Methods: Suffolk-cross ewes (n = 8) were allowed to come into estrus naturally and were euthanized 24 (n = 3), 36 (n = 3), or 48 (n = 2) hours after the onset of estrus. All visible follicles were measured, aspirated and pooled according to follicular diameter: small (<= 2.0 mm), medium (2.1-4.0 mm), large (4.1-6.0 mm), and preovulatory (> = 6.1 mm). Aspirated cells were separated from follicular fluid by centrifugation. Total RNA was extracted from cell pellets and reverse transcribed. The resulting cDNA was subjected to qPCR, using primer sets designed to amplify each variant specifically. Gene expression was normalized to that of beta–actin within samples, and compared by analysis of variance with the level of significant differences set at p < .05. Results: Relative expression of FSHR-3 exceeded that of both FSHR-1 and FSHR-2 in medium follicles, and tended to be higher in small follicles (p = .09) regardless of time after onset of estrus, and thus results from different time points were pooled. Expression of FSHR-3 was greater than that of FSHR-2 and luteinizing hormone receptor (LHR) in small and medium follicles. Expression of LHR was greatest in preovulatory follicles. Conclusions: These experiments show that in addition to the well characterized G protein-coupled form of the FSHR, alternatively spliced variants of the FSHR may participate in follicular dynamics during follicular waves of the sheep estrous cycle. Furthermore, these results indicate that an “alternatively” spliced form of the FSHR (FSHR-3) is the predominant form of the FSHR in the sheep.
Keywords: FSH receptor; Follicle development; Ewe; CIDR; Alternate splicing